An aetiological evaluation of short stature - Phirke, Deepa S.; Phirke, Sachin O.; Khot, Swati (International Journal of Research in Medical Sciences, 2017)
Background: Short stature can be a normal variant or secondary to an underlying disorder. It is necessary to evaluate short stature to differentiate a normal from pathological short stature and thus decide the further treatment needed. This study was conducted at a tertiary care hospital to find out the various etiologies of short stature Methods: An observational study was conducted on 49 children in age of 2-12 years with short stature. They were grouped as normal variants and pathological short stature depending on upper-lower segment ratio the study group was later divided into proportionate and disproportionate short stature. They were further investigated to find out the etiology of the short stature. The bone age of all groups was compared with the chronological age to calculate the bone age retardation. Results: Out of 49 children 26.5% were normal variants and 73.4% as pathological type. 77.7% of pathological short stature were proportionate type. The male:female ratio was 1:1.4. Chronic systemic disorders were detected in 24.48% while malnutrition and endocrine disorders constituted 12% each. The bone age retardation in endocrine disorders was 0.47. Conclusions: Chronic systemic disorders were commonest cause of pathological short stature in this study. Females were predominantly affected in all groups and bone age retardation was maximum in endocrine disorders, thus indicating that early diagnosis and management of these disorders is necessary to decrease the growth retardation in these children. An understanding of short stature not only permits to differentiate a normal variant from an underlying disorder but also helps in modifying the course by means of early intervention.